Body Percussion Video: Rhythmic Learning for Elementary School Students - Mastri Dihita Sagala; Zakarias Aria Widyatama Putra (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Research discusses the benefits of learning rhythm for elementary school students through videos. During the Covid-19 pandemic, teachers are required to be creative in providing online learning. Teachers are required to be able to use various kinds of internet technology which must be used effectively and usefully for the implementation of the learning process properly. During the COVID-19 pandemic, online learning is mandatory for all schools in Indonesia. The purpose of this research is to examine in depth the benefits of video-based learning given to elementary school students. The research method used is qualitative with a description approach through literature studies. All data collected is then processed and analyzed by presenting, verifying and concluding data. The results of this study indicate that music learning can be done through videos. Rhythmic as one of the elements of music can have a positive impact on children. Rhythmic learning through body percussion does not limit students to improve their motor skills and musicality. They can easily do body percussion learning through videos because students don't have to bother looking for musical instruments because their own bodies are used as sound sources. The addition of musical accent symbols to body percussion games also has a positive influence on students' sensitivity and motor skills. Another benefit is that learning through video can be done flexibly for students, as well as increasing independence and self-confidence for students.